Perjanjian Kerja Dalam Tradisi Leles di Desa Ngkiong Dora Kabupaten Manggarai Timur Provinsi Nusa Tenggara Timur Dari Perspektif Hukum Adat - Harmin, Tarsisius Sandriaka; Mauritsius, Darius; Pello, Helsina F (Artemis Law Journal, 2025)
Abstract: Employment agreements between people are one of the important aspects of human life. In Indonesia, employment agreements are regulated in positive law such as the Civil Code and a series of other laws and regulations. Labor agreements also develop in customary law. In Ngkiong Dora Village, East Manggarai, East Nusa Tenggara (NTT), there is a tradition of leles, which is a traditional work system based on agreements between its creators. However, in its implementation, leles has caused problems, namely violations of the agreement which are motivated by various reasons. The objectives of this research are to 1) find out the customary law regulation on work agreements in the Leles Tradition in Ngkiong Dora Village, East Manggarai Regency, NTT Province? 2) to know how to resolve disputes arising in the Leles Tradition in Ngkiong Dora Village, East Manggarai Regency, NTT Province from the perspective of customary law? 3) to know the protection of customary law against the rights of the parties in the Leles Tradition in Ngkiong Dora Village, East Manggarai Regency, NTT Province from the perspective of customary law? This research is an empirical legal research. This research was conducted in Ngkiong Dora Village, East Manggarai Regency. The types and sources of data in this research are primary data, secondary data and tertiary data. Respondents in this research are; tua teno, customary elders and farmers involved in the leles tradition in the past year. The data were analyzed descriptively qualitatively. Keywords: Customary Law; Employment Agreement, Leles Tradition.